A solution-processed MoS2/graphene heterostructure mediated by a bifunctional block copolymer as a non-noble metal platform for hydrogen evolution. Issue 11 (18th May 2022) - Plantzopoulou, Andriana; Sideri, Ioanna K.; Stergiou, Anastasios; Kafetzi, Martha; Pispas, Stergios; Arenal, Raul; Tagmatarchis, Nikos
Abstract : A molybdenum disulfide/graphene heterostructure exhibiting excellent HER performance was prepared and characterized. Abstract : Development of synthetic strategies towards two-dimensional laminar transition metal dichalcogenide/graphene heterostructures is of particular interest for the electrocatalytic hydrogen evolution reaction (HER). Herein, we describe the preparation of a molybdenum disulfide/graphene heterostructure, mediated by a bifunctional polystyrene- b -poly(acrylic acid) block copolymer. Surface engineering of graphene nanosheets by incorporation of ammonium-terminated organic chains facilitated attractive electrostatic interactions with the anionic polycarboxylate block of the copolymer, while the phenyl rings of the polystyrene block of the copolymer enabled the development of multiple van der Waals π–S interactions with the surface sulfur atoms of MoS2 . The heterostructure exhibits excellent HER performance, as a result of the synergistic effect of 1T-MoS2 loading onto graphene and the latter's charge delocalization efficiency. An onset overpotential value of −0.18 V vs. RHE, a small charge transfer resistance of 36.2 Ω and a large electrocatalytic surface area of 205 cm 2 were obtained, paving the way for the construction of advanced heterostructures based on graphene and transition metal dichalcogenides with improved electrocatalytic activity.